Ethan and the Future of Energy - Lee, Jong-hyun; Park, Sin-gu; Wan-Lau, Ruth (Singapore : WS Education and Hansol Education Co., Ltd., 2022)
Every book in the Future Of ... collection contains a fun story, a field trip, and a focus on a famous person. In this book, Ethan discovers solar energy. He visits Uncle Roy at a wind farm and learns all about renewable energy sources, and writes a school report on nuclear scientist, Enrico Fermi. Come learn all about energy with him, and be inspired!Discover, experiment and learn with the little scientists! Each little scientist has something new to teach readers. Through engaging narratives and full- colour illustrations, I'm a Little Scientist! introduces children to the exciting and ever-advancing world of science.Everyone can be a little scientist!
Keywords: Korean literature -- Translations into English; Renewable energy sources -- Juvenile literature